Statement of William Joyce Sewell - Sewell, William Joyce, 1835-1901.
Typewritten statement, signed by Sewell, regarding advances made in the nineteenth century and his hopes for the future.
U.S. senator from New Jersey, railroad official, and army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Progress; Army officers; Railroad officials; Senators, U.S. Congress -- New Jersey